Utilization of the Transparent Peer Review Policy to Train Graduate Pharmacy Students on Scientific Critique - Raed Ababneh (22155337) (2024)
Objective Recognizing the importance of training graduate students in scientific critique and peer review, we introduced an innovative instructional strategy using the transparent peer review policy (TPRP). This study aimed to explore students’ feedback and reflection on how published peer review reports influenced their scientific critique skills and thought process. Methods We used TPRP-adopting journals’ publicly available peer review reports for Master of Science in Pharmacy students, who analyzed real cases, including author submissions, reviewer comments, author rebuttals, editorial decisions, and final publications. A reflection assignment required students to share their insights on the TPRP-adopting journals’ review processes and how these influenced their scientific reviewing skills. Qualitative content analysis of the submitted reflections was conducted by two instructors not involved in developing or delivering this aspect of the course. Results Eleven students submitted reflections on their learning experiences through this public-facing peer review process. The analysis revealed that TPRP increased the students’ awareness of the peer review process and fundamental principles of scientific critique. Five key themes emerged: understanding research content, inspiring ideas, fostering objectivity, enriching peer review comprehension, and evaluating transparent peer review pros and cons. Students showed a positive attitude toward this pedagogical approach for acquiring the targeted skills. Conclusion We utilized peer review reports from TPRP-supporting journals as an educational tool, providing training on the fundamentals of peer review and scientific critique. This study suggests recommending TPRP-supported journal reports as a valuable educational tool for teaching scientific critique and peer review skills among graduate students. Other Information Published in: American Journal of Pharmaceutical Education License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.ajpe.2024.101268